2008
DOI: 10.1111/j.1939-1676.2008.00132.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tyrosine Kinase Inhibition by Imatinib Mesylate on Mast Cell Tumors in Dogs

Abstract: Background: Imatinib mesylate is a small molecule targeted at dysregulated protein-tyrosine kinase. Mutation of c-kit exon 11, which induces constitutive phosphorylation of KIT, is one of the mechanisms for the development or progression of mast cell tumor (MCT) in dogs. The purpose of this study was to examine the therapeutic potential of imatinib mesylate in canine MCT.Hypothesis: Imatinib mesylate has activity against MCT in dogs, and response to treatment can be correlated to presence of mutation within ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
95
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(101 citation statements)
references
References 18 publications
2
95
0
4
Order By: Relevance
“…Canine MCTs with activating mutations in exon 11 respond well to TKIs that are now readily available for dogs. 42,47,61,69,111 Furthermore, high-grade MCTs lacking mutations or aberrant KIT expression have been reported to respond better to a chemotherapy protocol composed of vinblastine and prednisone than to TKI. 140 Similar to the results in dogs, cats with MCTs harboring a mutation in exon 8 have also been reported to have a favorable response to TKIs.…”
Section: Detection Of C-kit Mutations For Prognosis and Therapeutic Dmentioning
confidence: 99%
“…Canine MCTs with activating mutations in exon 11 respond well to TKIs that are now readily available for dogs. 42,47,61,69,111 Furthermore, high-grade MCTs lacking mutations or aberrant KIT expression have been reported to respond better to a chemotherapy protocol composed of vinblastine and prednisone than to TKI. 140 Similar to the results in dogs, cats with MCTs harboring a mutation in exon 8 have also been reported to have a favorable response to TKIs.…”
Section: Detection Of C-kit Mutations For Prognosis and Therapeutic Dmentioning
confidence: 99%
“…Moreover, other studies reported that several TKIs with different chemical structures from imatinib induced objective tumour regression in canine MCTs with these mutations Hahn et al 2008;London et al 2009). However, several studies reported that clinical activity of imatinib against MCT could not be predicted based on the presence of mutations in exon 8 or 11 of c-kit (Isotani et al 2008;Bonkobara 2015) as in the cases described here.…”
Section: Discussionmentioning
confidence: 58%
“…Furthermore, in Dog 1, the result of IHC for KIT was strongly positive, supporting the likelihood of aberrantly activated KIT. Considering the recent reports that canine MCT can also be related to other mutations in exons 9, 13, and 17 of c-kit, and the platelet-derived growth factor receptor alpha (PDGFRA) gene, we suggest that future studies should focus on analysis of these genes as well as exons 8 and 11 of c-kit (Isotani et al 2008;Gregory-Bryson et al 2010). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A menor medida observada nos pacientes que responderam ao tratamento com mesilato de imatinibe foi alcança ao termino das 8 semanas de tratamento resultado diferente do observado por Isotani et al (2008) …”
Section: Macedo T Munclassified